Is Competitiveness a Question of Being Alike?: How the United Kingdom, Germany and Denmark Came to Compete through their Knowledge Regimes from 1993 to 2007 - Martin Møller Boje Rasmussen (Copenhagen Business School (CBS), 2014)
The present PhD-dissertation ” ”Is Competitiveness a Question of Being Alike? How United Kingdom, Germany and Denmark came to compete through their Knowledge Regimes from 1993 to 2007” studies the ideas which policy research organizations such as ministries of economics, economic councils and different types of think tanks – or what Campbell and Pedersen recently have defined as a nations knowledge regime – holds about the international competition of nations and what a nations competitiveness consists in, as well as whether and how these ideas co-varies with different national knowledge regimes particular form and organization. The primary argument and research result is, that even if the ideas, which policy research organizations in United Kingdom, Germany and Denmark in the period from 1993 to 2007 holds, in many ways are similar, they nonetheless exhibit nationally distinct features and differences. In short, the PhD-dissertation demonstrates, that not only does the organization of knowledge regimes vary. So do the ideas they produce.
hdl:10398/8972
Keywords: 650